Highly ordered amphiphilic cyclopalladated arylimine self‐assembly films for catalyzing Heck and Suzuki coupling reactions. (17th May 2016) - Zhao, Yaqing; Zhao, Na; Zou, Meiling; Li, Tiesheng; Li, Guoping; Li, Jinpeng; Wu, Yangjie
Abstract : A series of new cyclopalladated arylimine compounds (3a, 3b, 3c, 4a, 4b, 4c ) were synthesized and characterized. Their catalytic properties for Heck and Suzukicoupling reactions in a homogeneous system were preliminarily investigated using water as solvent, in which no ligands, air isolation or assistant solvents were needed incross‐coupling reactions . The optimization of the homogeneous system provided a basis for research on the heterogeneous catalytic reaction catalyzed by ordered self‐assembly films. Organized monolayers of3a, 3b, 3c were prepared and utilized as CC coupling catalysts. Monolayers of3a, 3b, 3c were deposited using Langmuir–Blodgett techniques and analyzed using π–A isotherms, UV–visible and X‐ray photoelectron spectroscopies andatomic force microscopy, which showed near orientation on the surface and stability under the optimized experimental conditions suitable for exploring Heck and Suzukicoupling reactions . The activity of immobilized3c monolayer is enhanced relative to homogeneous reaction, in which the ordered monolayers are efficient with a catalyst loading as low as 10 −5 mol%, turnover number as high as 79 200 and turnover frequency as high as 2640 h −1 . The catalytic efficiency is 100 times higher than that in the homogeneous case using the same amount and ratio of reagent. The increased activity of immobilized3c monolayer is due to a combination of its structure and changes in conformation when deposited onto the substrate. The topographic changes of catalyst films, stability of films andcatalytic activity were investigated withatomic force microscopy, cyclic voltammetry, X‐ray photoelectron spectroscopy andinductively coupled plasma atomicemission spectrometry, from which a heterogeneous catalytic mechanism for Suzukicoupling reaction is proposed. The study demonstrates that careful monolayer studies can provide useful models for the design and study of supported molecular catalyst systems. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A series of cyclopalladated arylimine self‐assembly films for catalyzing coupling reactions was synthesized, demonstrating that the utility of studying well‐characterized molecular monolayers can be used as models for supported molecular catalyst systems.